2013
DOI: 10.1089/dia.2012.0253
|View full text |Cite
|
Sign up to set email alerts
|

Does Pen Help? A Real-World Outcomes Study of Switching from Vial to Disposable Pen Among Insulin Glargine-Treated Patients with Type 2 Diabetes Mellitus

Abstract: Switching from insulin glargine vial-and-syringe administration to pen delivery resulted in improved treatment adherence and persistence, with comparable clinical and economic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
(49 reference statements)
0
38
0
Order By: Relevance
“…13,15 Low heterogeneity was estimated in this subanalysis. A nonnaïve population 23,26 showed a less marked trend, with important heterogeneity (I 2 = 80%; χ 2 significant). Baser et al 12 reported that mean change in MPR in patients who exchanged vial for pen device was 0.22 ± 0.01, compared with 0.13 ± 0.36 for those who continued on vial (P = .0011).…”
Section: Adherencementioning
confidence: 96%
See 3 more Smart Citations
“…13,15 Low heterogeneity was estimated in this subanalysis. A nonnaïve population 23,26 showed a less marked trend, with important heterogeneity (I 2 = 80%; χ 2 significant). Baser et al 12 reported that mean change in MPR in patients who exchanged vial for pen device was 0.22 ± 0.01, compared with 0.13 ± 0.36 for those who continued on vial (P = .0011).…”
Section: Adherencementioning
confidence: 96%
“…Six studies with a follow-up of 12 months were found, [13][14][15]18,19,26 with statistically significant difference in favor of pen ( Figure 2F), but important heterogeneity (I 2 = 89%) was detected. A subanalysis was performed using the studies with similar definitions of discontinuation threshold.…”
Section: Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…Based on published literature, treatment persistence was defined as the patient remaining on study drugs during the follow-up period, without discontinuation or switching after study drug initiation. [22][23][24][25][26] Study medication was considered discontinued if the prescription was not refilled within the expected time of medication coverage, defined as the 90th percentile of the mean time between the initial and second prescription fills, stratified by the metric quantity supplied between first and second fills among patients with at least 1 refill. Patients who restarted their initial medication during follow-up with the time period between 2 refills being greater than the "expected time of medication coverage" were considered nonpersistent patients.…”
Section: Follow-up Study Outcomesmentioning
confidence: 99%